Polyethylene glycol/mesoporous calcium silicate shape-stabilized composite phase change material: Preparation, characterization, and adjustable thermal property. (15th March 2015) - Qian, Tingting; Li, Jinhong; Min, Xin; Deng, Yong; Guan, Weimin; Ma, Hongwen
Abstract: Shape-stabilized composite phase change materials (ss-CPCMs) composed of PEG (polyethylene glycol) and MCS (mesoporous calcium silicate) were prepared by a facile blending and impregnating method. Various techniques were employed to characterize their structural and thermal properties. The supercooling extent, melting time and solidifying time of the ss-CPCM were respectively 25%, 28.2%, and 27.3% less than those of PEG. The characterization results by DSC (Differential Scanning Calorimetry) technique indicated that the PEG/MCS ss-CPCM was a good candidate for building applications due to its large latent heat, suitable phase change temperature, and good thermal reliability. The crystallinity of PEG in the ss-CPCMs decreased with the increase of MCS content. We proposed the possible formation mechanism of PEG/MCS and concluded that the thermal properties of the PEG/MCS were influenced by the adsorption confinement of the PEG molecule chains in the mesoporous structure of MCS and the interference of MCS as an impurity in the perfect PEG crystallization. Interestingly, the melting temperature of the new ss-CPCMs could be adjusted from 34.16 °C to 58.13 °C and the solidifying temperature could be adjusted from 27.21 °C to 44.10 °C. Corresponding latent heats of the melting and solidifying processes were 97.79–128.18 J/g and 85.41–114.19 J/g, respectively. Highlights: Novel PEG/MCS ss-CPCM was firstly prepared. Formation mechanism of PEG/MCS is systematically discussed. PEG/MCS has excellent thermal performance, outstanding thermal reliability and stability. Phase change temperatures can be tuned. Phase change enthalpies can be also tuned.